Вопрос:

5. Найти значение выражения \( 3 - 2\frac{2}{3} \cdot 6 \cdot \left( \frac{1}{2} - \frac{2}{3} : \frac{3}{5} \right) \).

Ответ:

Сначала решим \( \frac{1}{2} - \frac{2}{3} : \frac{3}{5} \). \( \frac{2}{3} : \frac{3}{5} = \frac{2}{3} \cdot \frac{5}{3} = \frac{10}{9} \). \( \frac{1}{2} - \frac{10}{9} = \frac{9}{18} - \frac{20}{18} = -\frac{11}{18} \). Выражение принимает вид: \( 3 - 2\frac{2}{3} \cdot 6 \cdot -\frac{11}{18} \). \( 2\frac{2}{3} = \frac{8}{3} \). \( \frac{8}{3} \cdot 6 = \frac{48}{3} = 16 \). \( 16 \cdot -\frac{11}{18} = -\frac{176}{18} = -\frac{88}{9} \). \( 3 - -\frac{88}{9} = 3 + \frac{88}{9} = \frac{27}{9} + \frac{88}{9} = \frac{115}{9} \). Ответ: \( \frac{115}{9} \).
Смотреть решения всех заданий с фото

Похожие